The fences of Chuschi: The impacts of land enclosure on an Andean indigenous community. (January 2023) - Bell, Karen; Hermoza, Rossi Taboada; Staddon, Chad; Willems, Bram; Maldonado, Fabiola Cárdenas; Berrocal, Noemí Tomaylla; Flores, Lisbeth Pariona
Abstract: In this study of the Andean town of Chuschi and its surrounding district of the same name, we consider the impacts of the proliferation of fencing on once open land. The paper contributes to a growing body of literature on the practice and impact of land fragmentation through fencing around the world, with positive and negative impacts having been noted. The analysis is based on 23 semi-structured interviews with community members and community leaders of Chuschi and the surrounding towns of Yanaccocha, Huaracco, Chaquiccocha, Pucruhuasi, Wacraccocha, Lerqona and Yupana. Some of the interviewees considered the fencing off of parcels of the communal land to be beneficial for land management, while others felt the practice was not ecologically or socially beneficial overall and created tensions in the community. In particular, some interviewees noted resentment towards those perceived to be 'ambitious' in terms of acquiring exclusive use of additional land. In conclusion, it appears that fencing, as practiced in Chuschi, may be a calculated approach to land management that some perceive to have overall collective benefits but, if not well governed, it also has the potential to be invasive and disruptive for communal Andean life. The paper addresses a gap in the literature on the motivations for, and impacts of, fencing in rural communities in Peru and contributes to wider debates on the social justice implications of enclosures. Highlights: A study of indigenous groups in the Andean town of Chuschi and surrounding district. Considers the impacts of the proliferation of fencing on once open land. Speaks to a debate on the practice and impact of land fragmentation through fencing. To date, there are very few of these studies in Latin America. The analysis is based on interviews with local community members and leaders. Some interviewees felt the fencing of once communal land caused grassland degradation. Some reported increasing tensions in the community arising from exclusive land use. Fencing, as practiced in Chuschi, may be a well calculated approach to land management that has some collective benefits. However, it needs to be well governed to avoid disruption to communal Andean life.